Maximising and evaluating the uptake, use and impact of golf and health studies. Issue 20 (19th December 2019) - Murray, Andrew; Kelly, Paul; Morton, Sarah; Glover, Danny; Duncan, Jennifer; Hawkes, Roger; Grant, Liz; Mutrie, Nanette
Abstract : Introduction: The dissemination of research, and evaluation of its impact is an increasing priority for the scientific community and funders. We take the topic of golf and health and aim to outline processes that may contribute to improved research uptake, use and impact proposing a research impact (RI) tool. We then evaluate our published research using the Research Contributions Framework (RCF). Methods: Building on existing research and frameworks we i) assessed the need for, ii) carried out and iii) published research, before iv) creating digital resources, v) sharing these resources widely and vi) evaluating our research. To evaluate uptake, use and impact of our three principal golf and health research outputs, we performed a contributions analysis, using the RCF first proposed by Morton. Results/Discussion: We developed a specific six-step Research Impact tool. Having implemented this, research uptake and use included over 300 press articles, a dedicated website and social media channels. Golf's global industry leadership dispersed information across >150 countries, embedded golf and health into curricula for industry professionals and used leading tournaments to promote health. National policy makers hosted dedicated meetings regarding golf and health and began to implement policy change. Conclusion: To date, strong uptake and use can be demonstrated for these studies, while a final contribution to impact requires further time to determine. Frameworks we used aiming to maximise impact (Research Impact tool) and evaluate its contribution to uptake, use and impact (Research Contribution Framework) could potentially add value to public health/sports medicine researchers.